Advanced epithelial ovarian cancer in the elderly: Chemotherapy tolerance and outcome - Efstathiou, E.; Dimopoulos, M.A.; Bozas, G.; Kastritis, E.; Moulopoulos, L.A.; Rodolakis, A.; Vlahos, G.; Gika, D.; Papadimitriou, C.; Bamias, A. (Anticancer Research, 2007)
Background: The prognostic significance of age in ovarian cancer has not been clarified. We investigated the characteristics of ovarian cancer presenting in ages >70 years and assessed the prognostic significance of advanced age. Patients and Methods: Four hundred and fifty-three patients with stage IIC-IV ovarian cancer (age>70 years n=106 [23%]), treated postoperatively with platinum-based chemotherapy were retrospectively reviewed. Results: Median overall survival (OS) of patients ≤70 years old (52.3 months, 95% CI: 43.2-61.3) was longer than that of older patients (38.8 months, 95% CI: 29.9-47.7) (p=0.005), but this difference was not significant in a multivariate analysis (p=0.978). Age >70 years was correlated with worse performance status (PS) (p=0.019), higher tumor grade (p=0.033), residual disease >2 cm (p=0.006) and less frequent paclitaxel administration (p<0.001). Toxicity from chemotherapy was similar between the two age groups, but the relative dose intensity of paclitaxel was lower among elderly patients. Conclusion: The worse outcome of ovarian cancer in elderly patients may be attributed to other associated adverse prognostic factors, but advanced age was not an independent prognostic factor.
Keywords: Chemotherapy; Elderly; Ovarian cancer; surgery